Strategi Bisnis Digital dan Kinerja Perusahaan Pada Usaha Mikro Kecil dan Menengah (UMKM) - Darmayania, K.D; Waisnayanti, N.P.A.L. Waisnayanti; Mariadi, C.I.N.; Dibya, M.S.; Widiantara, I.G.A.M. (P3M Politeknik Negeri Banjarmasin, 2023)
Digitalization has changed the way we work, communicate and access information by bringing advances in communication technology, data storage and automation processes. The influence of digitalization has an impact on micro, small and medium enterprises (MSMEs) in Indonesia. This study aims to determine the business paradigm shift in facing the digital era, sustainability strategy and the impact of the economic crisis due to the Covid-19 pandemic on MSMEs in Batam. The method used in this research is descriptive qualitative with case studies on MSMEs in Batam. The results found that (1) managerial ability has an influence on company performance; (2) sustainability strategy has an important role in company performance and (3) the impact of the economic crisis due to the Covid-19 pandemic affects the digitization of MSME products